Can cropping systems be energy efficient: Performance measure for various rice-based cropping systems in peninsular India - Shiladitya Dey; Kumar Abbhishek; Suman Saraswathibatla; Jayanarayanan Kuttippurath; Piyush Kumar Singh; Debabrata Das (Journal of Agriculture and Food Research)
Increasing non-renewable energy inputs and boosting environmental emissions while lowering economic returns are the primary concerns in agricultural cropping systems. This study assesses the energy consumption and ecological, environmental, and economic performance of traditional and alternative conservation rice-based cropping systems. Furthermore, the study also aims to identify the efficiency of resource use in rice-based cropping systems and the level of overused inputs. The cropping systems included in this study are conventional rice-maize-fallow (CR-CM-F), conventional rice-maize-cover crop (CR-CM-CC), conventional rice-rice-fallow (CR-CR-F), direct seeded rice-zero-tillage maize-fallow (DR-ZTM-F), direct seeded rice-zero-tillage maize-cover crop (DR-ZTM-CC), and direct seeded rice-rice -fallow (DR-DR-F). We have collected primary data from 1140 farmers through a face-to-face questionnaire survey from Andhra Pradesh, India. We have used the Data Envelopment Analysis (DEA) model to measure the technical efficiency and estimate the potential energy inputs saving under different cropping systems. Furthermore, the slack-based DEA (SBM-DEA) model is used to estimate the eco-efficiency of different production systems and the level of overused inputs in the case of conservation cropping systems. The results show that conservation cropping systems are more efficient and environmentally suitable compared to conventional systems. The study also finds that DR-ZTM-CC and DR-ZTM-F are more efficient in terms of economics, energy, and environmental impact than other production systems. The resulting mean eco-efficiency score of 0.68–0.76 for conservation cropping systems indicates considerable potential to reduce energy inputs (diesel fuel, machinery uses, and nitrogen fertilizer) and GHG emissions without sacrificing the crop yield in conservation cropping systems. The findings of this study have huge implications for energy optimization, leading to a net zero in the major cropping systems.